COMMUNITY PERCEPTIONS OF NON-CASH FOOD ASSISTANCE (BPNT) MANAGEMENT AND TARGETING IN MANGEMPANG VILLAGE, BARRU DISTRICT, BARRU REGENCY - Aminah, A.; Jumria; Marsuki (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal